EFFECTIVENESS OF WEBSITE-BASED VILLAGE GOVERNMENT INFORMATION SYSTEMS IN LIMBUNG VILLAGE SUNGAI RAYA SUBDISTRICT KUBU RAYA REGENCY - Rulida Yuniarsih; Bima Sujendra; Ksatriawan Zaenuddin (Halu Oleo University, 2025)
The development of information technology has encouraged the Indonesian government to implement e-government, including at the village level through the Village Information System (SID). This study aims to assess the effectiveness of the implementation of a website-based SID in Limbung Village, Sungai Raya District, Kubu Raya Regency. Using a descriptive qualitative approach, data was obtained through observation, interviews with village officials and the community, and documentation of the village's official website. The analysis focused on three indicators of effectiveness: timeliness, accuracy of targets, and cost accuracy. The results show that the effectiveness of the Limbung Village SID is still low. In terms of timeliness, content updates are very rare, causing information to lose its relevance. In terms of accuracy, many strategic features such as the Village Budget (APBDes), village reports, and regulations are not yet optimal, so that the public's need for information is not being met. In terms of cost-effectiveness, the benefits felt by the community are not yet commensurate with the costs. The main obstacles include limited human resources, weak ICT infrastructure, minimal socialisation, and low digital literacy among residents. Nevertheless, the SID still provides opportunities to strengthen transparency, participation, and village governance. This study recommends improving the capacity of the apparatus, consistency in content updates, and budget planning based on the actual needs of the community so that SID can function effectively as an e-government instrument at the village level.